Availability of dantrolene for the management of malignant hyperthermia crises: European Malignant Hyperthermia Group guidelines. (August 2020) - Glahn, Klaus P.E.; Bendixen, Diana; Girard, Thierry; Hopkins, Philip M.; Johannsen, Stephan; Rüffert, Henrik; Snoeck, Marc M.; Urwyler, Albert; ,
Summary: Faced with a malignant hyperthermia crisis, the immediate access to sufficient dantrolene is essential to achieve the best possible outcome for the patient. However, malignant hyperthermia crises are rare, and there may be administrative pressures to limit the amount of dantrolene stocked or, in some countries, not to stock dantrolene at all. There are no published guidelines to support anaesthetic departments in their effort to ensure availability of sufficient dantrolene for the management of malignant hyperthermia crises. After a literature review that confirmed a lack of clinical trials to inform this guideline, we undertook a formal consensus development process, in which 25 members of the European Malignant Hyperthermia Group participated. The consensus process used a modified web-based Delphi exercise, in which participants rated the appropriateness of statements that covered the dosing regimen for dantrolene in a malignant hyperthermia crisis, the types of facility that should stock dantrolene, and the amount of dantrolene that should be stocked. The resulting guidelines are based on available evidence and the opinions of international malignant hyperthermia experts representing a large group of malignant hyperthermia laboratories from around the world. Key recommendations include: the dosing regimen of dantrolene should be based on actual body weight, dantrolene should be available wherever volatile anaesthetics or succinylcholine are used, and 36 vials of dantrolene should be immediately available with a further 24 vials available within 1 h.